National And Universal Values In The Process Of Globalization - Jaloliddin Fozilov (Genius Journals, 2025)
This scientific article analyzes globalization and its impact on the national culture of society. Specific aspects, elements and foundations of trends arising on the basis of globalization are revealed.
Keywords: values; globalization; political reforms